A CONTRIBUTION TO BYZANTINE PROSOPOGRAPHY. 3. THE LACHANADES - Pantelis Charalampakis (Приноси към българската археология)
This study concerns individuals bearing the Byzantine family name Lachanas, which is attested in both literary and sigillographic sources as active mostly in the Balkans, Asia Minor, and the Aegean islands from the 11th to the 15th c. This essay consists of: an overview of the Lachanas name, its origin and variants; a short commentary on the known bearers of this name, their possible relations, and their presumable place in Byzantine society, with special attention paid to the seal of a Lachanas found recently in Plovdiv (published here for the first time) and its probable relation to another specimen presumably also from the same city; and a catalogue of individuals with the family name Lachanas.